Circumferential Endoscopic Submucosal Dissection of long-segment Barrett's Esophagus with Multifocal High-Grade Dysplasia - Sukrit Sud; Smruti Ranjan Mishra; Randhir Sud (Journal of Digestive Endoscopy, 2022)
In a case of long-segment Barrett's esophagus with multifocal high-grade dysplasia with multiple comorbidities, circumferential endoscopic submucosal dissection was performed. Following the procedure, the esophageal stricture was also managed.